Amazonian invaders in an Asian biodiversity hotspot : Understanding demographics for the management of the armoured sailfin catfish, Pterygoplichthys pardalis in Kerala, India - Smrithy Raj; Appukuttannair Biju Kumar; Rajeev Raghavan; Neelesh Dahanukar (Journal of Fish Biology, 2020)
Invasion of armoured catfish, Pterygoplichthys spp . , is a major threat to global aquatic biodiversity, and developing effective strategies for their control and eradication is both a concern and a research priority. A length‐based population assessment of invasive Pterygoplichthys pardalis in southern India, a hotspot for endemic aquatic biodiversity, indicated that rapid growth, high growth performance index and continuous recruitment have aided their successful invasion. Increasing fishing pressure on the adults is not adequate for population management, and only targeting young individuals (